2017 SME keynote; When Are Commodity Prices Going to Rise? - Douglas B. Silver (Society for Mining, Metallurgy & Exploration, 2017)
"Editor’s note: Douglas B. Silver, Portfolio Manager, Orion Resource Partners, was the keynote speaker at the 2017 SME Annual Conference & Expo in Denver, CO on Feb. 19, 2017. He also gave the keynote address to the SME Annual Conference in 2008. The following is his 2017 keynote address with a few of the slides that were presented. The full speech is available on YouTube https://www.youtube. com/watch?v=uF0qwGJIX3UIn 2008, I had the privilege of giving SME’s keynote address. At that time the financial markets were on the verge of collapse and my presentation described the issues. Unfortunately I was correct, and global markets went into a steep nosedive, creating the largest economic downturn since the Great Depression.In hindsight, there were plenty of signs that this was coming. The Supercycle had created massive new wealth. This wealth was largely invested in the United States due to the country’s political stability and credit worthiness. In 2004, the large investment banks convinced the U.S. Securities Exchange Commission (SEC) to allow them to triple their borrowing leverage ratios. This made the banks more vulnerable to market volatility. The banks then lent money to NINJAS - people with no income, no job and no assets. Even worse was the fact that these unqualified home owners used adjusted-rate mortgages (ARMs) which they, of course, intended to refinance prior to interest rates rising. These mortgages were then bundled up by the banks and sold to investors as “safe” investment products. The money flowed into these products because the rating agencies gave these instruments high marks. These same agencies earned their fees from the very same banks seeking high ratings. (No conflict there). Private debt exploded and peaked out in 2008.These mortgage products were sold in an unregulated shadow banking system and the ARMs came due. Toxic mortgage default rates skyrocketed and the mortgage-backed securities collapsed in value. This house of cards had a negative feedback loop that accelerated the market crash and resulted in more than $1.5 trillion being lost in the securitization sector, a 47 percent decline in the Dow Jones Industrial Average, foreclosure rates skyrocketing and housing prices collapsing. The financial markets were in a nosedive."